A comprehensive review of Siraitia grosvenorii (Swingle) C. Jeffrey: chemical composition, pharmacology, toxicology, status of resources development, and applications - Huang, Huaxue; Peng, Zhi; Zhan, Shuang; Li, Wei; Liu, Dai; Huang, Sirui; Zhu, Yizhun; Wang, Wei (Frontiers in Pharmacology, 2024)
Siraitia grosvenorii (Swingle) C. Jeffrey (S. grosvenorii), a perennial indigenous liana from the Cucurbitaceae family, has historically played a significant role in southern China's traditional remedies for various ailments. Its dual classification by the Chinese Ministry of Health for both medicinal and food utility underscores its has the potential of versatile applications. Recent research has shed light on the chemical composition, pharmacological effects, and toxicity of S. grosvenorii. Its active ingredients include triterpenoids, flavonoids, amino acids, volatile oils, polysaccharides, minerals, vitamins, and other microconstituents. Apart from being a natural sweetener, S. grosvenorii has been found to have numerous pharmacological effects, including alleviating cough and phlegm, preventing dental caries, exerting anti-inflammatory and anti-allergic effects, anti-aging and anti-oxidative, hypoglycemic, lipid-lowering, anti-depression, anti-fatigue, anti-schizophrenic, anti-Parkinson, anti-fibrotic, and anti-tumor activities. Despite its versatile potential, there is still a lack of systematic research on S. grosvenorii to date. This paper aims to address this gap by providing an overview of the main active components, pharmacological efficacy, toxicity, current status of development and application, development dilemmas, and strategies for intensive exploitation and utilization of S.grosvenorii. This paper aims to serve as a guide for researchers and practitioners committed to exploiting the biological resources of S. grosvenorii and further exploring its interdisciplinary potential.